2sinxcosx-cosx-sinx+1

0 голосов
112 просмотров

2sinxcosx-cosx-sinx+1


Алгебра (16 баллов) | 112 просмотров
0

здесь упростить?

0

если в задании нет ошибок, то вот как ниже, смотри

Дан 1 ответ
0 голосов

= 2sinxcosx - cosx - sinx +1= (cosx + sinx)^2 -( cosx +sinx) = (cosx + sinx)(cosx + sinx -1)
1. cosx= - sinx  делим на cosx не равный 0
tgx = -1
x= - п\4 + пn
2. cosx + sinx -1 =0
sqr(1- sin^2x) = 1-sinx

возводим в квадрат
1- sin^2x = 1 - 2sinx + sin^2x
2sin^2x - 2sinx = 0
sin^2x - sinx=0
sinx(sinx -1)=0,  sinx =0, x= пn
sinx=1 , x= п\2 + 2пn

(1.4k баллов)
0

готово